SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN CALON MAHASISWA BARU MENGGUNAKAN METODE AHP DAN SAW - Nurul Ramadhan; Sriani; Supiyandi (Smart Education, 2026)
New student admission is a process in educational institutions that screens prospective students according to established criteria. The new student admission process typically involves registration, file selection, and acceptance. However, the student admission selection process at the South Tapanuli Education Institute is still manual, making it difficult to select one candidate from among the prospective students. This problem gave rise to the idea of ??creating a decision support system to make accurate decisions regarding new student admissions in accordance with institutional policies. The parameters used in this decision support system are the average school exam score, academic potential test, parental income, and parental dependents. This decision support system was developed using a ranking technique using Simple Additive Weighting (SAW), weighting using the Analytical Hierarchy Process (AHP) technique. This method was chosen because it allows for the selection of the best alternative from various alternatives. The use of the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods in determining the passing of prospective new students allows for a more objective, transparent, and effective selection process, which ultimately improves the quality of student admissions and supports better decision-making in student admissions at the Tapanuli Selatan Institute of Education.